SIG PERSEBARAN JUMLAH TERNAK MENURUT KECAMATAN DI KOTA MALANG TAHUN 2018-2020 - Muhammad Ramdani Afi Pratama; Bambang Agus Herlambang, Ahmad Khoirul Anam (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2024)
One of the policies of the Malang City Livestock and Fisheries Service is to promote livestock production businesses and develop an information system about the distribution of livestock populations in each sub-district of Malang City in an integrated and comprehensive manner for the community. This WEBGIS-based livestock distribution information system in each region was created to support the policies of the Malang City Livestock and Fisheries Department and make it easier for people who want to know the development of the livestock population in Malang City and see which areas have the potential for dairy cattle, goat and buflalo production. existing in a particular area. The implementation of the information system developed through WEBGIS is capable of presenting information in the form of graphs and tables per type of livestock, per sub-district and per year. Presents a map of the distribution of livestock populations with color degradation, as well as presenting the location of livestock distribution points per district. Based on this, the stock of livestock in each region can be known so that the Malang Regency Livestock and Fisheries Service can estimate the level of livestock production in order to meet the community's need for meat.